Cross‐sectional study of propofol dose during intravenous sedation for dental surgery in patients with long‐term oral benzodiazepine therapy: A secondary publication - Toshiaki Fujisawa; Kazuki Miyata; Yukie Nitta; Akifumi Terui; Emi Ishikawa; Eri Hamaya; Keiichiro Wakana; Shigeru Takuma; Makiko Shibuya (Wiley, 2022)
Abstract Objectives The amount of propofol required for intravenous sedation (IVS) in patients on long‐term oral benzodiazepine (BZD) therapy may be affected by drug interactions and central changes in sensitivity. However, there is no research on the effect of long‐term oral BZD use on the amount of propofol required for IVS. We aimed to clarify the difference between the total propofol dose required for IVS in patients with or without long‐term oral BZD therapy. Material and methods Among patients treated for 4 years, the total administered dose required for IVS with propofol alone and local anesthesia for the extraction of bilateral impacted mandibular wisdom teeth, was retrospectively compared between patients with continuous oral BZD use for ≥6 months (BZD group; n = 24) and those without such use (control group; n = 307). The aimed sedation level was the Ramsay sedation scale 3-4. Results The amount of propofol required for IVS was significantly lower in the BZD group compared to the control group (4.83 ± 1.30 vs. 5.91 ± 1.25 mg/kg/h, p < .001; 95% confidence interval, −1.22 to −0.94 mg/kg/h; Cohen's d, 0.84). The required propofol dose was not influenced by preoperative oral BZD administration on the day of extraction (presence [n = 13] vs. absence [n = 11]: 4.9 ± 1.3 vs. 4.8 ± 1.7 mg/kg/h, p = .83). Long‐term oral BZD therapy remained a significant factor for a lower required propofol dose after adjusting for age with multiple linear regression analysis. The underlying mechanism cannot be an additive action process but might pertain to competitive inhibition via an enzyme involved in glucuronate conjugation or competitive albumin binding. Conclusions Clinicians should understand that patients on long‐term oral BZDs therapy might require less propofol for IVS than those not on BZDs, irrespective of whether BZDs were taken preoperatively on the day of surgery.